The Antagonists Test of Probiotic Bacteria Isolated from Black Tiger Shrimp (Penaeus monodon fabricus) Against Pathogens Pseudomonas sp, Aeromonas hidrophyla, Vibrio alginolyticus - Ranap Junani Sari; Feliatra '; Dessy Yoswaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
AbstractProbiotic bacteria are beneficial microbes that are beneficial to improve the microbialbalance in the digestive tract. The purpose of research to test the antimicrobial activity ofprobiotic bacteria in inhibiting the growth of pathogenic bacteria Pseudomonas sp,Aeromonas hidrophyla, and Vibrio algonolyticus. The method used in penilitian is a surveymethod, ie dengam observe and identify probiotic bacteria isolated from the gastrointestinaltract tiger shrimp (Penaeus monodon fabricus).The results showed that that the greatest inhibition zone strains of probiotic bacteriacontained in the code R10 is able to inhibit the activity of pathogenic bacteria P. stutzeri witha large zone of inhibition was 9.93 mm, the largest zone of inhibition of bacterial pathogensA. hydrophila is a probiotic bacterial strain with code R8 with a large zone of inhibition is9:46 mm, and most large inhibition zones of bacterial pathogens are present in V.alginolyticus strains of probiotic bacteria with the code R10 with a large zone of inhibitionwas 8.90 mm.Keywords : Probiotic Bacteri, Black Tiger Shrimp, Against Pathogens